Probabilistic methods for financial and marketing informatics - Neapolitan, Richard E.; Jiang, Xia. (San Fransisco, CA : Morgan Kaufmann Publishers, 2007)
Bayesian Networks are a form of probabilistic graphical models and they are used for modeling knowledge in many application areas, from medicine to image processing. They are particularly useful for business applications, ans * Unique coverage of probabilistic reasoning topics applied to business problems, including marketing, banking, operations management, and finance. * Shares insights about when and why probabilistic methods can and cannot be used effectively; * Complete review of Bayesian networks and probabilistic methods for those IT professionals new to informatics.
I: Informatics and Baysesian Networks; Introduction to Informatics; Basics of Probability and Statistics; Algorithms for Bayesian Networks; Decision Trees and Influence Diagrams. II: Business Informatics: Collaborative Filtering; Targeted Advertising; Market Basket Analysis; Venture Capital Decision Making; Measuring Operational Risk; Credit Scoring; Applications to Investment Science. Appendices.
Includes bibliographical references (p. 397-408) and index.
Keywords: Finance -- Statistical methods; Bayesian statistical decision theory -- Data processing; Marketing -- Statistical methods; Information technology; Electronic books